Morphological parallelism of sympatric cave-dwelling microsnails of the genus Georissa at Mount Silabur, Borneo (Gastropoda, Neritimorpha, Hydrocenidae) - Mohd Zacaery, Khalik; Esra, Bozkurt; Menno, Schilthuizen (Blackwell Verlag GmbH, 2019)
Parallel evolution in phenotype may result when closely related taxa are adapting in the face of similar ecological pressures. Here, we discuss possible parallelism in shell morphology in the context of the microgeographic phylogeography of two conchologically distinct sympatric hydrocenid snails inhabiting a limestone outcrop and its cave system, Georissa pyrrhoderma and Georissa silaburensis, respectively, at Mount Silabur in Sarawak, Malaysian Borneo. Our results show a certain degree of morphological parallelism of a third, possibly new, cryptic Georissa species within the same cave that strongly diverged from its above-ground sister species, G. pyrrhoderma. We found that both sympatric cave species have shifted from a more sculptured, conical shell toward a broader, less sculptured form.